Impact of body burden of pesticide residues on the reproductive tract of buffalo - KAUR, KARANPREET; GHUMAN, SARVPREET SINGH; SINGH, OPINDER; BEDI, JASBIR SINGH; GILL, JATINDER PAUL SINGH (The Indian Journal of Animal Sciences, 2016)
The disruption of reproductive system leading to infertility can occur due to accumulation of endocrine disrupting chemicals such as pesticide residues in the reproductive tract and ovarian follicular fluid after their entry into blood of animals. Infertile adult female buffalo (100) from a slaughterhouse were utilized to assess the presence of pesticide residues in their blood and reproductive tract as well as the microscopic alterations in the tract. The pesticide residues were detected in 25% blood, 43% reproductive tract and 32% ovarian follicular fluid samples by gas chromatograph (GC) and were confirmed by gas chromatograph-mass spectroscope (GC-MS). Compared to blood, the pesticide residues were high in reproductive tract. The concomitant presence of specific pesticide residues was observed in blood, reproductive tract and follicular fluid. Histopathological alterations in pesticide-negative as well as low and highly pesticide-positive reproductive tracts of slaughtered buffaloes were 0.25±0.71, 1.87±2.23 and 3.65±1.68/sample, respectively. The major alterations were leiomyosarcoma, haemangiosarcoma, cystic ovarian degeneration, fibrotic/atrophic ovaries and cyst adenoma. In conclusion, the presence of pesticide residues in the reproductive tract of female buffalo, may be a factor contributing towards infertility.